Integration of families in nursing care: a comparative study between different specialties - Pedro Sousa; Márcio Tavares; Maria Clarisse Louro; João Frade (Instituto Politécnico de Viseu, 2024)
Introduction: Nurses, regardless of specialty, must be qualified and capable of involving families in their clinical practice, promoting the training and empowerment of families in solving their problems, and promoting and maintaining family health. Objective: To compare nurses' attitudes towards the importance of involving families in care according to the area of the master's degree in nursing attended at a Portuguese nursing school. Methods: A quantitative cross-sectional study, descriptive and correlational, applied to 71 nurses attending a master's degree in nursing. The questionnaire includes the scale Importance of the Family in Nursing Care - Nurses' Attitudes. Results: Nurses who attend the master's degree course in Family Health Nursing have more attitudes towards partnership, coping, and inclusion of family in care and have a lower perception of the family as a burden. Nurses who attend the master's degree in Person in Critic Situation showed the least positive results towards involving families in nursing care. Conclusion: The nurses from all different master's degrees who participated in this study revealed a positive attitude toward the importance of including families in nursing care. The unique characteristics of the Master's in Family Health Nursing seem to improve communication, support, and integration of care towards families, thereby enhancing their practice in comparison to the other master's in nursing.